Artificial Organelles: Digital Microfluidic Platform for Proteoglycan and Glycoprotein Biosynthesis. (2010) - Martin, Jeffrey G.; Beaudet, Julie M.; Dordick, Jonathan S.; Linhardt, Robert J.
Abstract : The development of artificial organelles is a new, fast-growing field in which a variety of techniques have been employed. This article gives a brief overview of the history of artificial organelles, and describes the development of an artificial endoplasmic reticulum and Golgi organelle on a digital microfluidic platform. This device should be useful in high-throughput combinatorial proteoglycan/glycoprotein synthesis, providing critical information about the control of biosynthetic pathways for these important signaling molecules.